Fluoroquinolone-Associated Tendinopathy of the Hand and Wrist: A Systematic Review and Case Report. (September 2017) - Berger, Israel; Goodwin, Isak; Buncke, Gregory M.
Background: Fluoroquinolone use has been known to be associated with tendinopathy and tendon rupture for over 30 years. Hand and wrist involvement has been reported rarely, yet without early recognition and withdrawal of the fluoroquinolone, there is potential for significant morbidity.Methods: We searched Medline using a comprehensive search strategy for fluoroquinolones and tendinopathy of the hand and wrist, and provide a case report of a possible levofloxacin-related tendon rupture in a patient with a previous mutilating hand injury.Results: We located 10 previously reported cases of fluoroquinolone-associated tendinopathy in the hand or wrist ranging from 1983 to 2015. Unlike Achilles tendinopathy, women were no more likely than men to have tendon rupture affecting the hands or wrists. Our patient was a 59-year-old man with prior tendon repair but otherwise noncontributory medical history who experienced spontaneous tendon rupture on an extended course of levofloxacin and required extensive pulley and boutonnière repair.Conclusions: Given the extensive damage that may be caused to weakened tissue, clinicians should maintain a high index of suspicion of tendinopathy in patients taking fluoroquinolones who have had previous tendon repairs, particularly in the setting of unexplained changes in recovery trajectory.